An Experimental Study of the Feasibility of Identifying the Impact Damages of Reinforced Concrete Piers Using a Modal Frequency Method. (22nd January 2020) - Zhou, Xiwu; Zhang, Wenchao; Gao, Yushen; Zhang, Guoxue; Wen, Mengdan
Abstract : In this research study, horizontal impact tests were carried out on five reduced scale pier models using China's most advanced multifunctional ultrahigh heavy drop hammer impact test system and DHDAS dynamic signal acquisition and analysis system. Due to the fact that the traditional measurement method can only be used for local measurement damage, and the volatility is high, this paper proposes a test method for the modal frequency identification of the overall damage of reinforced concrete pier and applies the ultrasonic damage measurement method to verify the results. The tests analyzed the modal frequencies and ultrasonic velocity identifications for the purpose of evaluating the impact damages of bridge piers, as well as the relationship between them. The results showed that the modal frequencies were consistent with the ultrasonic waves in identifying and evaluating the damages to the piers. Also, the modal frequency damage factors were determined to be functions of the ultrasonic wave velocity damage factors. Therefore, the results of this study confirmed that it was feasible to characterize the impact damages of piers using a modal frequency method.